Persuasion Over Time: A Longitudinal Analysis of Message Strategy and Engagement in B2B Instagram using ELM - Astaningrum, Meita Dinar; Safitri, Reza; Oktaviani, Fitri Hariana (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2025)
The rise of mobile-first platforms has transformed how Business-to-Business (B2B) communication operates, including the persuasive mechanisms involved. Instagram, a platform typically associated with lifestyle content, is increasingly used by professionals and enterprises for branding and talent marketing. However, most persuasion models, including the Elaboration Likelihood Model (ELM), have not accounted for such digital shifts. ELM traditionally views persuasion as a single-message effect, underestimating the role of repetition, platform structure, and cumulative engagement. This study aims to examine the persuasive architecture of B2B content on Instagram through the case of @AcademyBINAR, an Indonesian digital education platform that adopted an enterprise communication strategy between June and December 2024. The research employs content analysis and linear trend regression to measure the prevalence of rational vs. emotional appeals and central vs. peripheral cues, alongside engagement trends over time. The findings reveal a dominance of rational appeals and central cues, coupled with statistically significant growth in likes, saves, and shares indicating that elaboration is not immediate, but cumulative. This study contributes to the theoretical refinement of ELM by proposing a temporally responsive framework in which professional persuasion is driven by consistency, message utility, and platform-specific repetition. It also offers practical insights for B2B content strategists operating in visual-first digital environments.